2005
DOI: 10.4049/jimmunol.174.8.5110
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Lymphocyte Death in Sepsis Occurs by both the Death Receptor and Mitochondrial Pathways

Abstract: Patients with sepsis are immune compromised, as evidenced by their failure to clear their primary infection and their propensity to develop secondary infections with pathogens that are often not particularly virulent in normal healthy individuals. A potential mechanism for immunosuppression in sepsis is lymphocyte apoptosis, which may occur by either a death receptor or a mitochondrial-mediated pathway. A prospective study of blood samples from 71 patients with sepsis, 55 nonseptic patients, and 6 healthy volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
287
0
11

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(315 citation statements)
references
References 45 publications
(64 reference statements)
17
287
0
11
Order By: Relevance
“…This has been illustrated by the description of increased mortality, decreased bacterial clearance, and altered pro-inflammatory immune response after polymicrobial septic challenge in mice lacking both T and B cells (119,120). A growing body of evidence has now confirmed that the lymphocyte-mediated immune response may be dysfunctional after severe sepsis and may play a major role in the development of a state of immunoparalysis in patients.…”
Section: Studies Of T-lymphocyte Subsetsmentioning
confidence: 98%
“…This has been illustrated by the description of increased mortality, decreased bacterial clearance, and altered pro-inflammatory immune response after polymicrobial septic challenge in mice lacking both T and B cells (119,120). A growing body of evidence has now confirmed that the lymphocyte-mediated immune response may be dysfunctional after severe sepsis and may play a major role in the development of a state of immunoparalysis in patients.…”
Section: Studies Of T-lymphocyte Subsetsmentioning
confidence: 98%
“…Le Tulzo et al concluded that lymphocyte apoptosis was rapidly increased in the blood of patients in septic shock and that this development of lymphocyte apoptosis led to a profound and persistent lymphopenia associated with poor outcome [28]. Hotchkiss's group observed that the frequency of apoptosis was substantially increased in CD4 + and CD8 + T-cells, B cells (CD20 + ), and NK cells (CD56 + ) in septic individuals when compared to non-septic patients and that the degree of lymphocyte apoptosis correlated with the severity of sepsis involving both (death receptor and mitochondrial) apoptotic pathways [29]. These experiments clearly supported the concept that lymphocyte apoptosis induced immune suppression during sepsis, mainly through a mechanism of direct depletion of cells of the adaptive immune system.…”
Section: Lymphocyte Apoptosis Suppresses the Immune Systemmentioning
confidence: 99%
“…Mice with defects in the Fas/Fas ligand signaling pathway through genetic engineering or pharmacological blockade show decreased levels of sepsis-induced lymphocyte apoptosis [111,112], as well as increased survival in the CLP model [113]. Furthermore, immunohistologic analyses and study of caspase activation patterns in apoptotic lymphocytes isolated from baboons with E. coli-induced septic shock [114] as well as a large series of human sepsis patients [115] are consistent with contributions from both the mitochondrial and death-receptor pathways of apoptosis. However, inhibition of B cell apoptosis by specific targeting of FccRII (CD32), an ITIM-containing Fc receptor, was insufficient to reduce mortality in the mouse CLP model, despite leading to a significant drop in apoptotic cells numbers [116].…”
Section: Induction Of Neutrophil Extracellular Trap-associated Cell Dmentioning
confidence: 99%